Myth Criticism: Theory and Practice - Dr. Indhu M. Eapen (International journal of economic perspectives, 2020)
This paper delineates the various perspectives of Myth Criticism. Myth critics believe that myths can be subjected to different analyses. Myths use depth language, which conveys many meanings and has profound significance. Though the standard reason offered for the creation of myths is that early human societies needed to explain the events of the physical world, and lacking any explanation for such phenomena as storms and earthquakes, they created supernatural beings endowed with immense powers; a few critics also believe that the stories of gods are echoes of a vastly superior extra-terrestrial culture that visited earth in the distant past.